Reconfiguration of supply chains: What are the priorities of German firms? - Cevat Giray Aksoy; Andreas Baur; Lisandra Flach; Beata K. Smarzynska Javorcik (CESifo GmbH, 2024)
At the height of the Covid-19 pandemic, global supply chains of firms came under increased public scrutiny. Pandemic-related production and transportation disruptions had put supply chains under severe pressure worldwide and were often associated with considerable economic costs. However, as the pandemic has subsided, the extent of supply chain disruptions has also decreased significantly. While eight out of ten German manufacturing firms reported material shortages at the height of the pandemic in December 2021, this share had fallen to 18 percent in October 2023. Nonetheless, the recent attacks by the Yemeni Houthi rebels on container ships in the Red Sea highlight the fact that supply chain risks remain significant.
Keywords: 330